2011
DOI: 10.4061/2011/264248
|View full text |Cite
|
Sign up to set email alerts
|

Predominant RET Germline Mutations in Exons 10, 11, and 16 in Iranian Patients with Hereditary Medullary Thyroid Carcinoma

Abstract: Medullary thyroid carcinoma occurs in both sporadic (75%) and hereditary (25%) forms. The missense mutations of RET proto-oncogene in MTC development have been well demonstrated. To investigate the spectrum of predominant RET germline mutations in exons 10, 11, and 16 in hereditary MTC in Iranian population, 217 participants were included. Genomic DNAs were extracted from the leukocytes using the standard Salting Out/Proteinase K method. Mutation detection was performed through PCR-RFLP and DNA sequencing. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 32 publications
3
33
2
Order By: Relevance
“…Linkage disequilibrium analysis of the correlation of 5 of the 13 SNP in the RET gene showed that SNP G691S in exon 11 (rs1799939) and SNP S904S in exon 15 (rs1800863) were in complete linkage disequilibrium, which is consistent with a previous report [23] . SNP G691S and S904S are associated with the development of MTC in patients who carry germline mutations of the RET gene [26][27][28][29] .…”
Section: Color Version Available Onlinesupporting
confidence: 81%
See 1 more Smart Citation
“…Linkage disequilibrium analysis of the correlation of 5 of the 13 SNP in the RET gene showed that SNP G691S in exon 11 (rs1799939) and SNP S904S in exon 15 (rs1800863) were in complete linkage disequilibrium, which is consistent with a previous report [23] . SNP G691S and S904S are associated with the development of MTC in patients who carry germline mutations of the RET gene [26][27][28][29] .…”
Section: Color Version Available Onlinesupporting
confidence: 81%
“…Exons 11 and 13 are important functional regions of the RET gene [3,10,22,23] . Among the 13 variants in this pedigree, except p.D707E, p.G691S in exon 11, and p.L769L and p.V778I in exon 13 are located in the region that also codes ITK.…”
Section: Color Version Available Onlinementioning
confidence: 99%
“…In USA the most common mutation in this gene was at codon 634 in patients with hereditary MTC (Moura et al, 2009). In Iran and China also the highest genetic variation and mutation was reported at codon 634 (Zhou et al, 2007;Hedayati et al, 2011). Thus, it seems that mutatio.n of codon 634 is the most common RET proto-oncogene mutation in MTC.…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, poorly differentiated (2,4) and anaplastic thyroid carcinoma account for 1-2% of thyroid malignancies. Medullary thyroid carcinoma (3%; MTC) is a malignancy of parafullicular C cells that are derived from neural crest and occurs in sporadic (75%) and hereditary (25%) types (5). This wide spectrum of progression has been closely linked with the pattern of cumulative genetic and epigenetic alterations, which are correlated with tumor differentiation, metastasis and invasion (6).…”
Section: Introductionmentioning
confidence: 99%